Silicon-Based RF Front-Ends for Ultra Wideband Radios - Safarian, Aminghasem (Springer, 2017)
Ultra-wideband (UWB) is a promising technology for high speed short distance communication, as well as low data-rate low power communication for object localization and sensor networks. The most important characteristic of UWB is the operation in power-limited regime while achieving high channel capacity. The main challenge lies in designing transceivers for wideband signals.